Prosthesis-Patient Mismatch after Surgical Aortic Valve Replacement: Neither Uncommon nor Harmless - Rayol,Sérgio da Costa (2019)
Abstract Prosthesis-patient mismatch (PPM) after surgical aortic valve replacement (SAVR) is an issue that has been overlooked (not to say neglected). Cardiac surgeons must bear in mind that this is a real problem that we must tackle. The purpose of this paper is to be a wake-up call to the surgical community by giving a brief overview of what PPM is, its incidence and impact on the outcomes. We also discuss the increasing role played by imaging for predicting and assessing PPM after SAVR (with which surgeons must become more acquainted) and, finally, we present some options to avoid PPM after the surgical procedure.